Bragg-curve imaging of 7 MeV protons in a lithium fluoride crystal by fluorescence microscopy of colour centres. (20th February 2018) - Nichelatti, E.; Piccinini, M.; Ampollini, A.; Picardi, L.; Ronsivalle, C.; Bonfigli, F.; Vincenti, M. A.; Montereali, R. M.
Abstract: A lithium fluoride crystal slab was irradiated in air with a proton beam of nominal 7 MeV energy at a linear accelerator that is under development at ENEA C.R. Frascati. The irradiation generated a spatial distribution of stable colour centres in the crystal that could be detected as a luminescent image under blue-light excitation in a fluorescence microscope. The reconstruction of the whole Bragg curve from the luminescent image is here demonstrated for the first time by taking into account finite proton-energy bandwidth and saturation of defect concentration due to high absorbed dose. The obtained results confirm lithium fluoride detectors based on visible photoluminescence of radiation-induced aggregate colour centres as reliable candidate devices for advanced proton-beam diagnostics.